2016
DOI: 10.1186/s40478-016-0379-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of patients with amyotrophic lateral sclerosis resulting in a totally locked-in state (communication Stage V)

Abstract: In the present study, we performed a comprehensive analysis to clarify the clinicopathological characteristics of patients with amyotrophic lateral sclerosis (ALS) that had progressed to result in a totally locked-in state (communication Stage V), in which all voluntary movements are lost and communication is impossible. In 11 patients, six had phosphorylated TAR DNA-binding protein 43 (pTDP-43)-immunoreactive (ir) neuronal cytoplasmic inclusions (NCI), two had fused in sarcoma (FUS)-ir NCI, and three had copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…The ophthalmoplegia and dysuria observed in our patients might be caused by involvement of the non-motor system including the frontal eye field and autonomic nervous centers in the brain 24,39 . Neuropathological evidences also support this idea 30,48,49 . Rapid body weight decline in the early stages of ALS might be the earliest non-motor manifestation due to multisystem neurodegeneration in ALS.…”
Section: Discussionsupporting
confidence: 52%
“…The ophthalmoplegia and dysuria observed in our patients might be caused by involvement of the non-motor system including the frontal eye field and autonomic nervous centers in the brain 24,39 . Neuropathological evidences also support this idea 30,48,49 . Rapid body weight decline in the early stages of ALS might be the earliest non-motor manifestation due to multisystem neurodegeneration in ALS.…”
Section: Discussionsupporting
confidence: 52%
“…Increased potentiation of the descending medial longitudinal fasciculus following corticospinal tract lesions was reported 31 . Pathologically, the presence of TDP-43 pathology in these tracts have been reported in some ALS autopsies 32,33 . These anterior horn cell-modulators may be involved in this "inverse" split-leg phenomenon.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, it was reported that p‐TDP‐43 pathology often spreads to the PNL system especially in Nishihira type 2 ALS cases, but usually without severe PNLD . Severely progressed cases might be associated with PNLD; in the reported p‐TDP‐43 positive ALS cases resulting in a totally locked‐in state, all of the six cases showed moderate to severe degeneration in the substantia nigra with presence of p‐TDP‐43‐positive NCIs . The pallidum and subthalamic nucleus were also degenerated with or without p‐TDP‐43‐positive NCIs.…”
Section: Discussionmentioning
confidence: 99%